2020
DOI: 10.1016/j.omtn.2020.09.013
|View full text |Cite
|
Sign up to set email alerts
|

SERCA Overexpression Improves Mitochondrial Quality Control and Attenuates Cardiac Microvascular Ischemia-Reperfusion Injury

Abstract: Despite significant advances in the treatment of myocardial ischemia-reperfusion (I/R) injury, coronary circulation is a so far neglected target of cardioprotection. In this study, we investigated the molecular mechanisms underlying I/R injury to cardiac microcirculation. Using gene delivery, we analyzed microvascular protective effects of sarcoplasmic/endoplasmic reticulum Ca 2+ -ATPase (SERCA) on the reperfused heart and examined the role of SERCA in regulating mitochondrial quality co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 67 publications
(73 reference statements)
1
96
0
Order By: Relevance
“…Studies have shown that endothelial cells are affected earlier and are more sensitive to heart ischemia injury than cardiomyocytes ( Singh et al, 2020 ; Wang et al, 2020a ). Microcirculation injury is one of the most important pathological mechanisms of ischemic injury ( Tan et al, 2020b Wang et al, 2020b ). Myocardial ischemic injury impairs the structure and function of endothelial cells, increases vascular tone, and leads to a decrease in cellular energy metabolism and ATP production ( Bøtker, 2019 ; He et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that endothelial cells are affected earlier and are more sensitive to heart ischemia injury than cardiomyocytes ( Singh et al, 2020 ; Wang et al, 2020a ). Microcirculation injury is one of the most important pathological mechanisms of ischemic injury ( Tan et al, 2020b Wang et al, 2020b ). Myocardial ischemic injury impairs the structure and function of endothelial cells, increases vascular tone, and leads to a decrease in cellular energy metabolism and ATP production ( Bøtker, 2019 ; He et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…MMP was assessed using the JC-1 mitochondrial membrane potential assay kit (C2006, Beyotime, Shanghai, China) as described in a previous study [42]. HUVECs were collected after treatment with melatonin in the presence of ox-LDL.…”
Section: Mitochondrial Membrane Potential (Mmp) Assessmentmentioning
confidence: 99%
“…Intracellular calcium measurements were performed as previously described with minor modifications [ 39 ]. Briefly, H9C2 cells were loaded with 5 μ M Fluo4-AM calcium probe for 30 minutes at 37°C [ 40 ]. Cells were then washed with PBS, and intracellular calcium was observed under a confocal laser scanning microscope (LSM780; Carl Zeiss, Oberkochen, Germany, or TCS SP8; Leica, Wetzlar, Germany) and an Axio Zoom V16 stereo microscope (Carl Zeiss) [ 41 ].…”
Section: Methodsmentioning
confidence: 99%